The Rate of Tetraploidy Determination in Rainbow Trout (Oncorhynchus Mykiss) in Embryonated Eggs - Ioan Bencsik; Nicolae Pacala; Gabi Dumitrescu; Dorel Dronca; Jana Stanculet; Liliana Petculescu-Ciochina; Liliana Boca (Scientific Papers Animal Science and Biotechnologies, 2023)
Polyploidy at fish is characterized by modification of normal diploid chromosome set (2n) to triploid (3n), tetraploid (4n) etc. Experiments were carried out on biological material from rainbow trout (Oncorhynchus mikiss) during the natural period of reproduction. Polyploidy can be induced by exposing the eggs to heat shock. The highest levels of embryo losses are observed in the first two decades of incubation. The success rate of the tetrapolidy induction after 6 hours after fertilization evaluated by karyotype analysis was 66.67%. During the whole incubation period for the experimental group the losses were evaluated at 39.86% from the incubated eggs, and for the control group at 13.48%.